Seed priming with antioxidants improves physiological parameters in sunflower cv. Co-2 under unfavourable germination conditions: SEED PRIMING WITH ANTIOXIDANTS IN SUNFLOWER UNDER UNFAVOURABLE GERMINATION - ASHWINI SAKPAL; A SABIR AHAMED; DEEPAK RAO (Journal of Oilseeds Research, 2022)
The results of studying the effects of sunflower seed priming with 4 different antioxidants at 2 different concentrations under three unfavourable germination are presented in this paper. The goal of the study was to determine the impact of antioxidants on the physiological performance of sunflower seeds under favourable and different unfavourable germination conditions. The findings showed that seed germination was more stressed at 40°C and 100% RH. The effect of stress was minimized by seed priming with Butylated hydroxy toluene 0.1% followed by Butylated hydhydroxy toluene 2 % by recording 7 and 4 per cent higher germination over control. The seedling growth parameters viz., root and shoot length, seedling dry matter production and vigour indices were influenced negatively by NaCl 0.1 % stress condition. Under unfavourable germination conditions, seed priming with Butylated Hydroxytoluene (BHT) at 0.1 per cent, followed by a- Tocopherol at 0.5 per cent, and Ascorbic acid at 1.0 per cent, was observed to improve seedling growth characteristics.